A thermodynamic framework linking phase assemblage to mix design optimization in mineral admixture-modified magnesium oxychloride cement - Tong Li; Huisu Chen; Tingting Zhang (Journal of Cleaner Production, 2026)

Dual-network hydrogel incorporating Cu/Zn-MOF and stem cell exosomes: Synergistic regulation accelerates wound healing in diabetic infected lesions - Bowen Cao; Zitong Tian; HuiSu; Peici Jia; Haiyu Li; Pengde Han; He Lin; Lei Xie; Xiao Huang; Zhangping Wang; Yong Huang (Chemical Engineering Journal, 2026)

Boundary exchange and benthic fluxes drive trace element cycling in North Pacific marginal seas - Xiaoyu Chen; Hyeryeong Jeong; Kongtae Ra; Huisu Lee; Intae Kim (Limnology and Oceanography, 2025)
Trace elements are essential micronutrients for primary producers in the ocean, supporting vital metabolic functions. However, their behavior in the northwestern Pacific remains unknown. This study investigated the behavior and benthic fluxes of Mn, Fe, Co, Ni, Cu, Zn, and Cd in the East/Japan Sea and the Yellow Sea. Rare earth element fractionations ([Nd/Er] PAAS and Ce/Ce* ratios) were used to trace scavenging and water mass inputs. In the East/Japan Sea, trace element distributions were categorized into three categories. Mn, Fe, and Co were influenced by atmospheric deposition in surface waters and benthic input, with fluxes of 742, 96, and 0.8 μ mol m −2 yr −1 , respectively. Ni and Cu were depleted from surface waters and had a limited influence from benthic inputs. Zn and Cd were regulated by biological activity. Zn concentrations ranged from 0.6 to 1.5 nmol kg −1 at the surface, peaked at 6.8–11.8 nmol kg −1 at a depth of 500 m, and decreased to 3.5–7.9 nmol kg −1 at the bottom. Zn correlated positively with in the upper 500 m but negatively at greater depths, likely owing to shelf inputs. In the Yellow Sea, all trace elements exhibited a vertically conserved distribution owing to rapid water mixing. These results contribute to the current biogeochemical understanding of the region by providing higher‐resolution cross‐transect investigations and report the decoupling of Zn– in the East/Japan Sea for the first time.

Guidelines for zirconium tolerance in Li-ion battery cathode recycling from manufacturing scraps - Huisu Jeung; Gigap Han; Chan Mi Jeon; Kyungjung Kwon (Chemosphere, 2025)

Assessment of several carbon-based materials as cathode amendment on stimulating oxygen reduction reaction catalytic in microbial fuel cells - Huong V.H. Tran; Bonyoung Koo; Sunghoon Son; Hyungwon Chai; Sena Park; Huisu Im; Sokhee P. Jung (Journal of Water Process Engineering, 2025)

Optimization of operation time and efficiency in microbial electrolysis cells based on anode performance and operation time - Sunghoon Son; Bonyoung Koo; Hyungwon Chai; Huisu Im; Sokhee P. Jung (Journal of Water Process Engineering, 2025)

Thermodynamic mechanism of silica dosage and temperature on phase composition of well cement at high temperature and its impact on macro-properties - Huiting Liu; Tong Li; Jiaying Zhang; Pu Xu; Xiujian Xia; Yongjin Yu; Lin Liu; Huisu Chen (Applied Geochemistry, 2025)

Development of DEM–ANN-based hybrid terramechanics model considering dynamic sinkage - Ji-Tae Kim; Huisu Hwang; Ho-Seop Lee; Young-Jun Park (Journal of Terramechanics, 2024)

Modafinil exerts anti-inflammatory and anti-fibrotic effects by upregulating adenosine A2A and A2B receptors - Haiyan Li; Ji Aee Kim; Seong-Eun Jo; Huisu Lee; Kwan-Chang Kim; Shinkyu Choi; Suk Hyo Suh (Purinergic Signalling, 2024)

Rational design of hybrid sensor arrays combined synergistically with machine learning for rapid response to a hazardous gas leak environment in chemical plants - Wonseok Ku; Geonhee Lee; Ju-Yeon Lee; Do-Hyeong Kim; Ki-Hong Park; Jongtae Lim; Donghwi Cho; Seung-Chul Ha; Byung-Gil Jung; Heesu Hwang; Wooseop Lee; Huisu Shin; et al. (Journal of Hazardous Materials, 2024)

Fabrication and characterization of chitosan-pectin emulsion-filled hydrogel prepared by cold-set gelation to improve bioaccessibility of lipophilic bioactive compounds - Hyunjong Yu; Huisu Kim; Pahn-Shick Chang (Food Chemistry, 2024)

The Atmospheric Input of Dissolvable Pb Based on the Radioactive 210Pb Budget in the Equatorial Western Indian Ocean - Huisu Lee; Jaeeun Lee; Hyunmi Lee; Intae Kim (Journal of Marine Science and Engineering, 2023)
To estimate the atmospheric deposition flux of 210Pb in the equatorial western Indian Ocean, we determined the dissolved ( 0.45 μm) in the water column. In addition, we calculated the atmosphere-derived dissolvable Pb in seawater using the budget of 210Pb. The dissolved 210Pb and total 210Pb were higher in the surface layer and, overall, showed a decreasing distribution with depth. In particular, radioactive 210Pb activities in the surface-to-upper layer (

Distributions of Radiocesium and Plutonium in the Korean Seas and North Pacific after the Fukushima Accident, 2011–2014 - Jaeeun Lee; Suk Hyun Kim; Huisu Lee; Hyunmi Lee; Intae Kim (Journal of Marine Science and Engineering, 2022)
The distributions of artificial radionuclides, radiocesium (134Cs and 137Cs) and plutonium isotopes (238Pu and 239+240Pu), in the surface water around the Korean seas (East/Japan Sea and Yellow Sea) in 2011–2012 and in three sections in the North Pacific between 2011 and 2014 were examined. The 137Cs activities in the surface water in the Korean seas in 2011 (immediately after the Fukushima nuclear power plant (NPP) accident on 17 March 2011) were comparable or not significantly different relative to those in 2010 and 2012. However, 134Cs, which had been not detected in the study area before the Fukushima accident (under the detection limit of 0.1 mBq kg−1 level), were detected rapidly in 2011 after the accident (in about 60% of the 72 samples) and gradually disappeared due to their short half-life (t1/2 = 2.06 years) in 2012 (detected in about 16% of the 24 samples). In addition, the highest activities of radiocesium and Pu isotopes appeared locally in some stations of the Korean Strait region (located between Korea and Japan) within 1–2 months immediately after the accident. This suggests that the radioactive nuclides released immediately after the Fukushima accident were significantly introduced through the atmosphere, based on recent studies conducted in neighboring areas. We also showed that the spatial distribution of radiocesium in the North Pacific moved eastward from 2012 to 2014, and we attempted to quantify the residence time of radiocesium (137Cs) in the Korean seas based on the long-term (tens of years scale) temporal trends of 137Cs activity data, which have been collected since the 1960s and 1970s. The estimated retention time of 137Cs in the East/Japan Sea and Yellow Sea were 25 ± 0.6 and 8.0 ± 0.1 years, respectively. These results are expected to be used as a preliminary study for a potential future event of a marine radioactive accident (which, of course, cannot be predicted) and as basic data for predicting the influences of radionuclide releases in the ocean.

Can environmental awards stimulate corporate green technology innovation? Evidence from Chinese listed companies - Huisu Lai; Fengying Wang; Chong Guo (Environmental Science and Pollution Research, 2022)

Adverse pregnancy outcomes in healthcare workers: a Korean nationwide population-based study - Chulyong Park; Mo-Yeol Kang; Dohyung Kim; Jaechan Park; Huisu Eom; Eun-A Kim (International Archives of Occupational and Environmental Health, 2017)

Sodium Sulfite Enhances Rhinovirus-Induced Chemokine Production in Airway Epithelial Cells - Yoon Hong Chun; Hyun Sook Kim; Huisu Lee; Sulmui Won; Jong-seo Yoon; Hyun Hee Kim; Jin Tack Kim; Joon Sung Lee (Bulletin of Environmental Contamination and Toxicology, 2012)